(untitled) (The Journal of Psychology and Sociology, 2018)
Assessing physical activity in Kazakhstan university students and identifying its predictors may help plan, advocate and implement effective public health interventions. This cross-sectional survey of 889 students of all years of study at al-Farabi Kazakh National University was completed in May 2017. Selected variables were tested in adjusted logistic regression models to predict regular physical activity (RPA) or walking 6 km every day. Sixty-one percent of female and 54% of male students (p<0.05) walked 6 km a day. 54% of female and 72% of male students (p<0.001) exercised at least 3 times a week for 40 min. Being a male (adjusted odds ratio (OR) 2.04 (95% confidence interval (CI) 1.47;2.84) and sleeping for 8 hours predicted RPA (OR 1.47 (95% CI 1.07;2.01)). Alcohol use (OR 0.44 (95% CI 0.30;0.65)), waterpipe smoking (OR 0.53 (95% CI 0.37;0.75) and sleeping 8 hours (OR 1.67 (95% CI 1.20;2.33)) predicted walking 6 km a day or more. Identified health disparity between female and male students should guide public health interventions in the university students’ community. Key words: physical, training, university, health behavior, tobacco, students